Male and female alcohol consumption and live birth after assisted reproductive technology treatment: a nationwide register-based cohort study. Issue 2 (August 2017) - Vittrup, Ida; Petersen, Gitte Lindved; Kamper-Jørgensen, Mads; Pinborg, Anja; Schmidt, Lone
Abstract: The objective was to assess the potential association between female and male alcohol consumption and probability of achieving a live birth after assisted reproductive treatment. From a nationwide Danish register-based cohort information on alcohol consumption at assisted reproductive treatment initiation was linked to information on births and abortions. From 1 January 2006 to 30 September 2010, 12, 981 women and their partners went through 29, 834 treatment cycles. Of these, 22.4% and 20.4% led to a live birth for female abstainers and heavy consumers (>7 drinks/week), respectively. Concerning men, 22.6% and 20.2% of cycles resulted in a live birth for abstainers and heavy consumers (>14 drinks/week), respectively. No statistically significant associations between alcohol consumption and live birth were observed. Adjusted odds ratios from trend analyses were 1.00 (95% confidence interval (CI) 0.99–1.01) and 0.99 (95% CI 0.97–1.01) for every one-unit increase in female and male weekly alcohol consumption at assisted reproductive treatment initiation, respectively. In conclusion, this study did not show significant associations between male or female alcohol consumption and odds of live birth after assisted reproductive treatment.